Synthesis of PVA/SiO2 Nanofibers by Electrospinning Method for Supercapacitor Separators - Muhamad Nirwan; Heru Setyawan; Widiyastuti Widiyastuti (Institut Teknologi Sepuluh Nopember, 2020)
In this research, polyvinyl alcohol (PVA)/silica nanofibers have been synthesized using electrospinning technique. Solutions of sodium silicate (Na2SiO3) in water and PVA flakes were blended and then processed by electrospinning method to obtain PVA/silica nanofibers. The effect of silica concentration on the resulting morphology and diameter of as-spun nanofibers were investigated by using scanning electron microscopy (SEM). The electrolyte uptake and retention of the as-spun nanofibers were measured. The silica concentration has an effect on the resulting nanofibers, where an increase in silica concentration resulted in a decrease on the diameter of the fibers. The manufactured nanofibers have an average diameter of 200-300 nm. The electrolyte uptake and retention values are also affected by the concentration of the silica in the electrospun solution, with the electrolyte uptake and retention values decreasing with the increase in silica concentration. The best values obtained are 151% for electrolyte uptake and 60% for electrolyte retention, which shows potential for PVA/silica nanofibers as an alternative material for supercapacitor separators.